Impact Of Covid 19 On The Psychology And Education Of Adolescents - Sunja, Angelicca (Jurnal Pendidikan Kesehatan, 2022)
The impact of the Covid 19 pandemic is an interesting issue to discuss, considering that the Covid 19 pandemic is a new disease phenomenon that occurs throughout the world. The existence of the Covid 19 pandemic has an impact on the psychology and education experienced by teenagers. This study aims to explain the impact of Covid-19 on psychology and education in adolescents. National and international journals are searched through Google Scholar, and Scient Direct 2015 sampai 2020. After searching according to the inclusion, exclusion and PEOS framework criteria, selected using the JBI Critical Appraisal tools found 10 journals that are ready to be analyzed. The results showed that 5 articles showed the impact of Covid 19 on increasing stress and anxiety on adolescent psychology, and 5 articles showed the impact of Covid 19, namely limitations on facilities and infrastructure, limited internet access hampered learning and online teaching for youth education. . The contributing design study used a quasi-experimental, quantitative and cross-sectional study which showed significant results of analysis and testing. It can be concluded that Covid 19 has an impact on the psychology and education of adolescents. This study can be used as an effort to prevent and treat psychological and educational problems experienced by adolescents.